THE CREATION OF GUPAY PANGWANOH DANCE ACCORDING TO HOMI BHABHA’S THEORY OF HYBRIDITY - Dyah Nuraini, Ajeng; Nursilah; Humaeroh; Ayu Rizki Ramadhani, Anjani; Zahratul, Siera; Jaya Putri, Jitera (International Journal of Performing Arts (IJPA), 2023)
Hobby K Bhabha identified that the theory of Poscononialism is a branch of critical theory that focuses on the colonial experience based on the point of view of a colonized society, systematically postcolonialism means something that has a concern in the national culture after the departure of imperial power which is a branch of study of cultural studies focused on socio-cultural analysis. Homi K bhabha identified that within the Posconoloneonial there appears cross-cultural in society in forms such as attitudes and cultures that enter and are called Hybridity. In this case, it will be reviewed from the Gupay Pangwanoh Dance Works to reveal which aspects are Hybridity. As a methodological tool, the author uses the PLH method where this method is an empowerment that we do consists of a process of socializing lectures on brainstorming demonstrations and imitation. From this journal, the author found the identification of Hybridity in the Pangwanoh Gupay Dance, especially in the aspect of movement in the dance.